2018
DOI: 10.1097/sla.0000000000002889
|View full text |Cite|
|
Sign up to set email alerts
|

Liver Transplantation and Hepatic Resection can Achieve Cure for Hepatocellular Carcinoma

Abstract: As other malignancies, statistical cure can occur for HCC, primarily with LT and secondarily with HR, depending on waiting-list capabilities and efficacy of tumor recurrence therapies after resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
128
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(132 citation statements)
references
References 30 publications
4
128
0
Order By: Relevance
“…14 However, a plateau may be visualized for survival curve after long-term follow-up, and this indicates the presence of cured subjects. [14][15][16] This is particularly true for patients with early-stage, resected lung adenocarcinomas. Given the long-term censored survival time of patients with clinical stage IA, resected adenocarcinomas, it was deemed reasonable to apply the cure model to these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 However, a plateau may be visualized for survival curve after long-term follow-up, and this indicates the presence of cured subjects. [14][15][16] This is particularly true for patients with early-stage, resected lung adenocarcinomas. Given the long-term censored survival time of patients with clinical stage IA, resected adenocarcinomas, it was deemed reasonable to apply the cure model to these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The cure model can capture the relationship between the covariates and long-term survivorship, 15 and it has been applied to oncology patients with various pathologic conditions for whom a cure is statistically plausible. [16][17][18] The covariates used in the mixture cure model were identical to those used in the Cox regression analysis. Cure fraction, which is the probability of being cured, was estimated for each nodule type.…”
Section: Discussionmentioning
confidence: 99%
“…Among all possible strategies to treat HCC, LT offers the best chance of cure. 9 Unfortunately, the number of available grafts is insufficient for all potential candidates. For this reason, LT is reserved for patients who will benefit most.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…We have already shown that the 'cure fraction' after transplantation for HCC is 74.1% compared to only 24.1% in the cases undergoing resection. 15 In the near future we hope to be able to add a figure for 'likelihood of cure' at the individual patient level, to the ERASL model.…”
Section: Issues Surrounding the Albi Scorementioning
confidence: 99%